Altered β1, 6‐GlcNAc branched N‐glycans impair TGF‐β‐mediated Epithelial‐to‐Mesenchymal Transition through Smad signalling pathway in human lung cancer. Issue 10 (9th June 2014) - Li, Na; Xu, Haineng; Fan, Kun; Liu, Xijun; Qi, Jingjing; Zhao, Chao; Yin, Peng; Wang, Liying; Li, Zengxia; Zha, Xiliang
Abstract The change of oligosaccharide structure has been revealed to be crucial for glycoproteins' biological functions and cell biological characteristics. N‐acetylglucosaminy transferase V (GnT‐V), a key enzyme catalysing the reaction of adding β1, 6‐N‐acetylglucosamine (GlcNAc) on asparagine‐linked oligosaccharides of cell proteins, has been implicated to a metastastic‐promoting oncoprotein in some carcinomas. However, this correlation might not be subjected to all types of cancers, for example, in non‐small cell lung cancers, low level of GnT‐V expression is associated with relatively short survival time and poor prognosis. To explain the role of GnT‐V in lung cancer progression, we studied the association of GnT‐V expression with lung cancer EMT behaviour. We found that GnT‐V expression was correlated with epithelial marker positively and mesenchymal marker negatively. GnT‐V levels, as well as β1, 6‐GlcNAc branched N‐glycans, were strongly reduced in TGF‐β1‐induced EMT of human lung adenocarcinoma A549 cells. Further studies showed that suppression of β1, 6‐GlcNAc branched N‐glycans by inhibitor or GnT‐V silencing in A549 cells could promote TGF‐β1‐induced EMT‐like changes, cell migration and invasion. Meanwhile, overexpression of GnT‐V impaired TGF‐β1‐induced EMT, migration and invasion. It suggests that GnT‐V suppresses the EMT process of lung cancer cells through inhibiting the TGF‐β/Smad signalling and its downstream transcription factors in a GnT‐V catalytic activity–dependent manner. Taken together, the present study reveals a novel mechanism of GnT‐V as a suppressor of both EMT and invasion in human lung cancer cells, which may be useful for fully understanding N‐glycan's biological roles in lung cancer progression.